2018
DOI: 10.2478/hukin-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Early and Senior Level Participation in International Women’s and Men’s Handball

Abstract: International competitions at the youth elite level have become an important part of attempts to identify, foster and develop sporting talent. However, sports science scholars disagree strongly about the value and importance of such competitions because little is known about the relationship between early performance, at both the team and individual level, and later success in adult elite sports. The first aim of this study was therefore to explore the relationship between international match experience at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
5
14
0
Order By: Relevance
“…The observed tendency of a decrease in the RAE at the senior level mirrors similar findings from other studies of team sports [32] and individual disciplines [33,34]. This suggests that the advantages athletes gain due to their early maturational development gradually decrease as they transition towards professional sport [2,35]. In addition, our study showed https://doi.org/10.1371/journal.pone.0230133.g001…”
Section: Plos Onesupporting
confidence: 90%
See 1 more Smart Citation
“…The observed tendency of a decrease in the RAE at the senior level mirrors similar findings from other studies of team sports [32] and individual disciplines [33,34]. This suggests that the advantages athletes gain due to their early maturational development gradually decrease as they transition towards professional sport [2,35]. In addition, our study showed https://doi.org/10.1371/journal.pone.0230133.g001…”
Section: Plos Onesupporting
confidence: 90%
“…Successful talent identification and development (TID) systems are regarded by policy makers as vital to achieving success in adult elite sports, and are based usually on the selection of athletes for special activities, teams and/or competitions [1]. The introduction of international competitions at the youth elite level, for example, has become an important part of identifying, fostering and developing sporting talent in elite development systems [2], and serves as a mechanism for recognising sporting excellence [3]. However, attempts to identify sporting talent often conflate athletes´future potential with their current performance [4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies have shown, RAEs across selection to formal TID programmes in Swedish football [13]; German football [14, 15]; international football [16]; English Rugby League [17]; Swiss alpine skiing and tennis [18]; German handball [19]; Spanish handball [20, 21]; and international handball [22, 23]. In addition, recently, Bjørndal, Luteberget and Holm [24] investigated the relationship between early and senior level participation in international male and female handball in Norway. It was found that players that participated at the junior international team level are significantly more likely to have played more senior international team matches than players who did not participate at the junior level.…”
Section: Introductionmentioning
confidence: 99%
“…It has to be noted, however, that physical performance in handball is different in the morning from what it is in the evening ( Pavlović et al, 2018 ). Studies related to the national teams of two of the world’s major countries in this sport – Norway and Denmark – have confirmed that experience in the Norwegian national youth and junior teams is associated with the number of international matches played in the senior category ( Bjorndal et al, 2018 ), and that the relative age effect is apparent in Danish national men’s teams at these younger levels ( Wrang et al, 2018 ). Regarding the training programs, it has been found that programs targeted at the inspiratory muscles not only improve these muscles in particular, but also contribute to enhancing aerobic performance ( Hartz et al, 2018 ) and postural stability exercises implementing the biofeedback method on stabilo and dynamometric platforms are practical and justifiable in junior goalkeepers ( Wilczyński, 2018 ).…”
mentioning
confidence: 95%